Formulation Development of Oral Mucoadhesive CoatedTerbutaline Sulphate Tablets Using Some Natural MaterialsExtracted from Edible Fruits Available in India: Formulation of oral mucoadhesive terbutaline tablets - Ranabir Chanda,; Lila Kanta Nath,; Sontosh Mahapatra, (Iranian Journal of Pharmaceutical Sciences, 2009)
Mucoadhesive polymers that bind to the gastric mucin or epithelial cell surface are useful in drug delivery for the purpose of increasing the intimacy and duration of contact of drug with the absorbing membrane. Several synthetic polymers are in use for this purpose. Since the biodegradability of the synthetic polymers are questionable, in this investigation, an oral mucoadhesive controlled delivery system has been developed for terbutaline sulphate using natural mucoadhesive materials extracted from edible fruits like Zizyphus mauritianaand Aegle marmelosthathave better mucoadhesive property than synthetic polymer hydroxypropylmethyl-cellulose K4M (HPMCK4M). The in vitroadhesive and mucoadhesive strength and swelling property of mucoadhesive materials extracted from edible fruits of Z.mauritianaand A. marmeloswere evaluated and compared with HPMCK4M by Share stress and Wilhelmy plate method. Different formulations of oral mucoadhesive coated terbutaline sulphate tablets were prepared using these natural materials and HPMCK4M and hardness, thickness, friability, weight variation and assay of tablets were tested. The in vitrorelease of terbutaline sulphate was studied in buffer pH 7.2at 37±0.5 ᵒC. The blood plasma concentration of terbutaline sulphate in rabbits was determined using HPLC. It was found that mucoadhesive materials extracted from edible fruits of Z. mauritianaand A. marmelos exhibited better adhesiveness andmucoadhesiveness as compared with the synthetic mucoadhesive agent HPMCK4M by different methods. The in vitroand in vivodrug release study of terbutaline sulphate exhibited extended drug release profile for tablets prepared with natural materials than synthetic polymers. Afterin vitro and in vivocorrelation study, it was seen that both in vitroand in vivodrug release study showed the same release profile. The present study shows that natural mucoadhesive materials extracted from edible fruits of Z. mauritianaand A. marmelos have greater mucoadhesive property than HPMCK4M where both are used in the same amount.